Ketertarikan Muda Mudi pada Media Sosial Instagram: Studi Kasus Barombong Kecamatan Tamalate Kota Makassar - Mrs. Nurlela; Mr. Asmunandar (Rayhan Intermedia, 2022)
This study aims to determine the interest of young people in social media Instagram, the implications and values ​​for society. This study uses qualitative research methods with observation techniques, in-depth interviews, and in-depth analysis to obtain the desired data. Interviews were conducted with several informants who have different backgrounds and are active in using Instagram social media and have been using Instagram for more than 5 years. The results of this study indicate that: (1) young people's interest in social media Instagram is different and has its own characteristics. (2) Instagram users can have a positive or negative impact depending on the user and how to use it. One way to make Instagram use positive is to limit Instagram usage and to prevent users from wasting their productive time, users can take advantage of the